Striking stabilization of Rana catesbeiana ribonuclease 3 by guanidine hydrochloride. Issue 6 (8th February 2013) - Solé, Magali; Brandt, Wolfgang; Arnold, Ulrich
Abstract : Unfolding by chemical denaturants and the linear extrapolation method are widely used to determine the free energy of proteins. Ribonuclease 3 from bullfrog shows an extraordinary behavior in guanidinium hydrochloride in comparison to its homologues ribonuclease A and onconase with a high transition midpoint of denaturation but an apparently low cooperativity. The analysis of the interdependence of thermal, urea‐, and guanidine hydrochloride‐induced unfolding revealed that whereas addition of urea resulted in the expected destabilization of all three proteins, guanidine hydrochloride acted diversely: in contrast to ribonuclease A and onconase, both of which were destabilized as expected, low concentrations of guanidine hydrochloride significantly stabilize ribonuclease 3 from bullfrog. This stabilizing effect was endorsed by in silico docking studies. Abstract : ► Thermal, urea‐, and GdnHCl‐induced unfolding of three homologous proteins is studied. ► The transition temperature decreases linearly as a function of urea concentration. ► T m of RNase A and onconase decrease linearly with GdnHCl concentration. ► RC‐RNase 3 is clearly stabilized by low concentrations of guanidine hydrochloride. ► Docking studies reveal a strong binding of the guanidinium ion to RC‐RNase 3.